“It Just Gives You Another Look on Things”: Using Adolescent Literature to Construct Inquiry and Deconstruct Social Stereotyping - Sarah A Bonner; Robyn Seglem (Middle Grades Review, 2016)
In the current climate of standardization, areas such as social justice are often overlooked as the pressures of covering the learning standards increase. Within today’s classrooms, it is imperative that teachers encourage curiosity, creativity, and student voice. Using a blend of both traditional literacy and new literacies, students in a rural junior high setting worked to establish a classroom environment dedicated to critical thinking and debunking social conventions related to both the prison system and gang life. This social justice exploration allowed students to be immersed in a variety of texts that empowered them to discuss and question a system that faces them currently. By providing a platform of inquiry, students cultivated their own understandings related to social justice and formulated new meanings that led to the dissemination of topic-related stereotypes.